2016
DOI: 10.1371/journal.pone.0163673
|View full text |Cite
|
Sign up to set email alerts
|

Association between Density of Coronary Artery Calcification and Serum Magnesium Levels among Patients with Chronic Kidney Disease

Abstract: BackgroundThe Agatston score, commonly used to quantify coronary artery calcification (CAC), is determined by the plaque area and density. Despite an excellent predictability of the Agatston score for cardiovascular events, the density of CAC has never been studied in patients with pre-dialysis chronic kidney disease (CKD). This study aimed to analyze the CAC density and its association with serum mineral levels in CKD.MethodsWe enrolled patients with pre-dialysis CKD who had diabetes mellitus, prior cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…In vitro analysis revealed that magnesium inhibits phosphate‐induced calcification in human aortic vascular smooth muscle cells dose dependently possibly by inhibiting Wnt/β‐catenin signaling, a key mediator of osteogenic differentiation and that magnesium can prevent hydroxyapatite crystal growth. In line with this, we reported that coronary artery calcification density was inversely associated with serum magnesium levels, particularly in patients with CKD and higher serum phosphate levels . Moreover, a large nationwide prospective cohort study of Japanese patients on hemodialysis showed that hypomagnesemia was significantly associated with an increased risk of mortality .…”
Section: Potential Solutions For Vascular Calcification In the Futuresupporting
confidence: 70%
See 1 more Smart Citation
“…In vitro analysis revealed that magnesium inhibits phosphate‐induced calcification in human aortic vascular smooth muscle cells dose dependently possibly by inhibiting Wnt/β‐catenin signaling, a key mediator of osteogenic differentiation and that magnesium can prevent hydroxyapatite crystal growth. In line with this, we reported that coronary artery calcification density was inversely associated with serum magnesium levels, particularly in patients with CKD and higher serum phosphate levels . Moreover, a large nationwide prospective cohort study of Japanese patients on hemodialysis showed that hypomagnesemia was significantly associated with an increased risk of mortality .…”
Section: Potential Solutions For Vascular Calcification In the Futuresupporting
confidence: 70%
“…In line with this, we reported that coronary artery calcification density was inversely associated with serum magnesium levels, particularly in patients with CKD and higher serum phosphate levels. 22 Moreover, a large nationwide prospective cohort study of Japanese patients on hemodialysis showed that hypomagnesemia was significantly associated with an increased risk of mortality. 23 This study also revealed that an increase in serum phosphate level elevated the cardiovascular mortality risk in the lower-and intermediate-Mg groups, whereas no significant risk increment was observed in the higher Mg group (P interaction = .03).…”
Section: Magnesium Supplementationmentioning
confidence: 99%
“…Limited information is currently available on the effects of Mg on arrhythmia, but Alabd et al reported that the post-dialysis QTc interval duration inversely correlated with a decrease in serum Mg levels during the HD session [61]. Table 1 shows observational studies that examined the relationship between serum Mg levels and cardiovascular calcification/atherosclerosis in CKD/ESRD patients [32,[62][63][64][65][66][67][68]. Most of these studies indicated an association between hypomagnesemia and cardiovascular lesions.…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%
“…Most of these studies indicated an association between hypomagnesemia and cardiovascular lesions. Sakaguchi et al performed a cross-sectional study to evaluate coronary artery calcification using multidetector-row computed tomography in 109 pre-dialysis CKD patients with DM [67]. A multivariate analysis showed that serum Mg levels were inversely associated with the density of coronary artery calcification, after adjustments for demographics, renal function, and indices related to nutrition, inflammation, and mineral and bone disorders.…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%
“…[14][15][16][17][18] Recently, there is increased interest in the role of magnesium in human CKD-MBD. Magnesium is an essential mineral for numerous intracellular processes, 19 but also an inhibitor of vascular calcification [20][21][22] and the release of profibrotic cytokines. 23 Hypomagnesemia is a risk factor for death, [24][25][26][27][28] and possibly for kidney function decline in human CKD patients.…”
Section: Introductionmentioning
confidence: 99%